2005
DOI: 10.1186/1475-2891-4-11
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quercetin on SW480 human colon carcinoma cells: a proteomic study

Abstract: Background: High fruit and vegetable intake is known to reduce the risk of colon cancer. To improve understanding of this phenomenon the action of different phytochemicals on colon cells has been examined. One such compound is quercetin that belongs to the group known as flavonoids. The purpose of this study was to determine the influence of quercetin on the proteome of the SW480 human colon adenocarcinoma cell line, specifically to identify proteins that could be the molecular targets of quercetin in its amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…It is advocated in the literature that a high intake of fruit and vegetables significantly reduced the risk of colon cancer, possibly through the protective action of quercetin (Mouat et al, 2005). In our study there was indication of fruit consumption in both sexes, hence reducing colon disease.…”
Section: Discussionsupporting
confidence: 56%
“…It is advocated in the literature that a high intake of fruit and vegetables significantly reduced the risk of colon cancer, possibly through the protective action of quercetin (Mouat et al, 2005). In our study there was indication of fruit consumption in both sexes, hence reducing colon disease.…”
Section: Discussionsupporting
confidence: 56%
“…Hoon Park et al have recently shown that the anticarcinogenic effects of quercetin might be due to its ability of inhibiting the h-catenin/Tcf signaling via the decrease of nuclear h-catenin/Tcf-4 proteins (52). In other studies, quercetin has been found to inhibit cell growth and to induce apoptosis in colon cancer cells by downregulating the Akt pathway and ErbB2/ ErbB3 (receptor tyrosine kinases) signaling (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally high consumption of fruit and vegetables is associated with reduced risk of ischaemic heart disease 10 and during a highvegetable diet, quercetin levels rise significantly. 11 In our study there was fruit consumption albeit principally limited to apple, banana and orange, closely followed by mango, strawberry and watermelon.…”
Section: Discussionmentioning
confidence: 99%